THE ROLE OF THE SHARIA SUPERVISORY BOARD AND THE SIZE OF ISLAMIC BANK ON THE PERFORMANCE OF SHARIA BANKS IN INDONESIA - Muhamad Bayu (Journal of Management and Islamic Finance, 2023)
This study aims to examine the role of the Sharia Supervisory Board and the size of Islamic banks on the performance of Islamic Commercial Banks in Indonesia. The characteristics of the Sharia Supervisory Board (SSB) are proxied by the variables of the size of the SSB, Concurrent Positions of the SSB, the Meetings of the SSB and the Educational Background of the SSB. This study used panel data of Islamic commercial banks from 2015 to 2020 using purposive sampling. The data analysis technique used panel data regression through the common effect model using the software views. The test results show that the variables of SSB concurrent positions, SSB meetings, educational background SSB and the size of the bank significantly affect the performance of Islamic commercial banks. Meanwhile, the size of the SSB have no effect on the performance of Islamic commercial banks. Multiple positions have a positive effect on the direction of the relationship, while the SSB meeting and SSB educational background have a negative effect on the performance of Islamic commercial banks.